(untitled) (Kronika Bydgoska, 2012)
The Internet is surely the latest and the most extensive medium in the history of the world. For the First time, the role of sender and the role of receiver are identical. They can be used practically for any purpose. One of them is promotion of a product, an idea or a place. Bydgoszcz was down on its luck in the past and it distinguished itself with attractive media facts in collective awareness. Communication between citizens and the authorities is defective as well. The Internet creates an opportunity for an interest in the city. Is it properly used? Do the Internet operations of the authorities of all levels, publishers and big companies, what’s on the Internet, popularise Bydgoszcz? There are ups and downs. Even the local govemment authorities couldn’t use the Internet as a forum for discussion with the residents, not to mention advertising.